Mute LVT floor and production process

Silent LVT floors are prepared through layered composite technology, and the sound absorption effect is improved by using nanocomposite materials, which solves the problem of poor silent performance of existing stone plastic floors and achieves significant sound absorption and noise reduction function.

CN119749008AActive Publication Date: 2025-04-04JIANGSU ZHONGXIN HOME NEW MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411944697.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing stone plastic floor has poor silent performance, which limits its application in multiple fields.

Method used

Silent LVT floors are prepared using laminated composite technology, including PVC wear-resistant layer, bonding layer and base layer. The nanocomposites are scattered, reflected and refracted during the sound wave propagation process to improve the sound absorption effect.

Benefits of technology

It significantly improves the sound absorption and noise reduction function of the silent LVT floor, effectively reducing the echo of falling objects and walking noise, creating a quiet and comfortable indoor environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119749008A_ABST
    Figure CN119749008A_ABST
Patent Text Reader

Abstract

The invention discloses a mute LVT floor and a production process. The mute LVT floor is formed by laminating and compounding a PVC wear-resistant layer, a bonding layer and a backing material layer, the PVC wear-resistant layer is prepared from the following components: PVC powder, a plasticizer and a nano composite material; the bonding layer adopts a modified polyurea bonding agent; the backing material layer is prepared from the following components: stone powder, PVC powder and a plasticizer; the main component of the prepared mute LVT floor is polyvinyl chloride, and the polyvinyl chloride is an environment-friendly nontoxic renewable resource and does not contain harmful substances such as formaldehyde, so that the indoor environment is formaldehyde-free and odorless after the floor is paved, and the health of residents is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flooring, in particular to a sound-proof LVT flooring and a production process. Background Art

[0002] Flooring is a common floor decoration material in home decoration. There are many types of flooring, each with its own characteristics. Solid wood flooring, also known as log wood flooring, is a flooring made directly from solid wood. It has the characteristics of natural wood, such as natural color, smell and texture, and is elegant and noble in decoration. It is a high-end decoration material. At the same time, solid wood flooring can regulate indoor temperature by absorbing and releasing moisture, and has the effect of sound insulation and heat insulation.

[0003] However, the decreasing global forest resources have led to a tightening supply of wood. The annual total demand for forest reserves in China is far greater than the logging quota, leaving a large gap. It is expected that the supply of solid wood flooring materials will be in short supply for a long time in the future.

[0004] With the improvement of people's living standards and the improvement of living environment requirements, the demand for wooden flooring has increased significantly. Therefore, stone plastic flooring has been increasingly used as a substitute, which can greatly alleviate the pressure on wood resources.

[0005] However, the soundproofing performance of the stone plastic floor prepared by the prior art is relatively general, which limits its application in many fields.

[0006] Therefore, the present invention solves the corresponding problems by providing a silent LVT floor. Summary of the invention

[0007] The object of the present invention is to provide a sound-proof LVT floor to solve the deficiencies in the prior art.

[0008] The technical solution adopted by the present invention is as follows:

[0009] The soundproof LVT floor includes: a PVC wear-resistant layer, an adhesive layer, and a base material layer which are laminated and compounded;

[0010] The PVC wear-resistant layer is made of the following ingredients by weight: 50-60 parts of PVC powder, 10-15 parts of plasticizer, and 8-12 parts of nanocomposite material;

[0011] The bonding layer adopts: modified polyurea adhesive;

[0012] The base material layer is made of the following ingredients by weight: 30-35 parts of stone powder, 30-35 parts of PVC powder, and 10-12 parts of plasticizer.

[0013] As a further technical solution: the method for preparing the nanocomposite material is:

[0014] First, carbon nanotubes are uniformly dispersed in deionized water to obtain a carbon nanotube dispersion, the pH of the carbon nanotube dispersion is adjusted to 9.8, the temperature is adjusted to 80° C., and the dispersion is kept warm for later use;

[0015] Adding sodium silicate to deionized water, stirring and mixing evenly to obtain a sodium silicate solution;

[0016] The sodium silicate solution is added dropwise to the carbon nanotube dispersion while stirring. After the addition is completed, stirring is continued for 1 hour, and the mixture is allowed to stand for 2 hours. Then, aluminum sulfate and sodium hydroxide are added and stirring is continued for 1 hour. Then, the pH value of the system is adjusted to neutral, and the mixture is allowed to stand for 4 hours. The mixture is subjected to high-speed centrifugation for 30 minutes, filtered, washed with water, dried, calcined at high temperature, and cooled to obtain a nanocomposite material.

[0017] As a further technical solution: the mass fraction of the carbon nanotube dispersion is 20-22%;

[0018] The concentration of sodium silicate solution is 2-2.5 mol / L;

[0019] Adding the sodium silicate solution dropwise into the carbon nanotube dispersion at a silicon dioxide / carbon nanotube mass ratio of 1-1.5%;

[0020] The amount of aluminum sulfate and sodium hydroxide added is such that the mass ratio of aluminum oxide to carbon nanotubes in the control system is 3-4%;

[0021] High-speed centrifugal speed is 8000r / min;

[0022] The high temperature calcination temperature is 550-600°C and the time is 40 minutes.

[0023] As a further technical solution: the preparation method of the modified polyurea binder is:

[0024] First, the composite polyether polyol is added into a reaction kettle, and then isophorone diisocyanate is added into the reaction kettle, and stirred for reaction to obtain a prepolymer;

[0025] Add urea and bis(4-aminophenyl) disulfide to dimethylacetamide, stir and mix well to obtain an intermediate;

[0026] The intermediate was added to the prepolymer, the temperature was adjusted to 80° C., the mixture was stirred for 30 minutes and cooled to room temperature to obtain a modified polyurea binder.

[0027] As a further technical solution: the molar ratio of the composite polyether polyol to isophorone diisocyanate is 3:1;

[0028] The mixing ratio of urea, bis(4-aminophenyl) disulfide and dimethylacetamide is 10 g:4 g:100 mL;

[0029] The mixing mass ratio of the prepolymer to the intermediate is 1:5-6.

[0030] As a further technical solution: the preparation method of the composite polyether polyol is:

[0031] Add diethylene glycol to the reactor, and then add soybean oil, castor oil and water, adjust the temperature to 78°C, keep warm and stir for 30 minutes, then add sucrose, pass nitrogen into the reactor, exhaust the air in the reactor, evacuate to 0.5Pa, then pass dimethylamine, adjust the temperature to 98°C, and then add propylene oxide dropwise while stirring. After the addition is completed, heat to 120°C, continue stirring for 40 minutes, adjust the pressure to 0.3MPa, the temperature to 112°C, continue to keep warm and stir for 4 hours, and then dry for 1 hour to obtain a composite polyether polyol.

[0032] As a further technical solution: the weight parts of the raw materials of the composite polyether polyol are respectively:

[0033] 5 parts of diethylene glycol, 12 parts of soybean oil, 18 parts of castor oil, 4.5 parts of water, 25.5 parts of sucrose, 1.2 parts of dimethylamine, and 51.3 parts of propylene oxide.

[0034] As a further technical solution: the plasticizer is dioctyl terephthalate.

[0035] The production process of the silent LVT floor includes: hot pressing the PVC wear-resistant layer, the adhesive layer and the base material layer to obtain a slab;

[0036] The slab is then cured for 12 hours, then rolled with UV paint, tempered, cured for 24 hours, and then punched, trimmed, coated and packaged to complete.

[0037] As a further technical solution: the hot pressing temperature is 145-150°C and the pressure is 8-10MPa;

[0038] The health-preserving temperature is 25°C;

[0039] The lamination is carried out by using a self-adhesive EVA film for lamination packaging.

[0040] Beneficial effects:

[0041] The main component of the sound-proof LVT floor prepared by the present invention is polyvinyl chloride, which is an environmentally friendly, non-toxic, renewable resource. It does not contain harmful substances such as formaldehyde. After paving, the indoor environment is formaldehyde-free and odorless, ensuring the health of residents.

[0042] The surface of the silent LVT floor is a wear-resistant layer, which can improve the durability of the floor. At the same time, the silent LVT floor prepared by the present invention has good sound absorption and noise reduction functions, can effectively reduce the echo of falling objects and walking noise, and create a quiet and comfortable indoor environment for users.

[0043] When sound waves are transmitted into the silent LVT floor, the nano-composite material will scatter the sound waves, change the direction of sound wave propagation, increase the number of reflections and refractions of the sound waves inside the silent LVT floor, thereby increasing the attenuation of the sound waves and enhancing the sound absorption effect.

[0044] Nano-composite materials can not only fill the pores and defects inside the silent LVT floor material, reduce the pore size, and increase the density of the silent LVT floor, but also make the propagation path of sound waves in the silent LVT floor more tortuous, thereby improving the sound absorption performance of the silent LVT floor.

[0045] The nanocomposite particles prepared by the present invention can form a special interface structure with the matrix of the silent LVT floor, such as the composite nanoparticles forming nanodomains or nanophases in the silent LVT floor, and these interface structures can absorb and dissipate sound wave energy.

[0046] Nanocomposite particles have a high specific surface area and surface energy, and can interact strongly with sound waves, converting the mechanical energy of sound waves into other forms of energy such as heat and dissipating it. This can further improve the sound absorption effect of the silent LVT floor on sound waves.

[0047] The invention uses a modified polyurea adhesive to bond the wear-resistant layer and the base material layer together, thereby greatly improving the bonding strength of the floor and providing durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 This is a curve of sound absorption coefficient at different sound wave frequencies. DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0050] The soundproof LVT floor includes: a PVC wear-resistant layer, an adhesive layer, and a base material layer which are laminated and compounded;

[0051] The PVC wear-resistant layer is made of the following ingredients by weight: 50-60 parts of PVC powder, 10-15 parts of plasticizer, and 8-12 parts of nanocomposite material;

[0052] PVC powder brand: TYH-2500M;

[0053] The PVC wear-resistant layer is prepared by putting the above materials into an internal mixer, mixing at 185°C, and then calendering through a five-roll calender;

[0054] The bonding layer adopts: modified polyurea adhesive;

[0055] The base material layer is made of the following ingredients by weight: 30-35 parts of stone powder, 30-35 parts of PVC powder, and 10-12 parts of plasticizer. The base material layer is mixed in an internal mixer at 185°C and then rolled in a four-roll calender.

[0056] PVC powder brand: TYH-2500M;

[0057] The stone powder particle size is 300 mesh, purchased from Hebei Chonghuang New Material Technology Co., Ltd.;

[0058] The preparation method of nanocomposite material is as follows:

[0059] First, carbon nanotubes are uniformly dispersed in deionized water to obtain a carbon nanotube dispersion, the pH of the carbon nanotube dispersion is adjusted to 9.8, the temperature is adjusted to 80° C., and the dispersion is kept warm for later use;

[0060] Adding sodium silicate to deionized water, stirring and mixing evenly to obtain a sodium silicate solution;

[0061] The sodium silicate solution is added dropwise to the carbon nanotube dispersion while stirring. After the addition is completed, stirring is continued for 1 hour, and the mixture is allowed to stand for 2 hours. Then, aluminum sulfate and sodium hydroxide are added and stirring is continued for 1 hour. Then, the pH value of the system is adjusted to neutral, and the mixture is allowed to stand for 4 hours. The mixture is subjected to high-speed centrifugation for 30 minutes, filtered, washed with water, dried, calcined at high temperature, and cooled to obtain a nanocomposite material.

[0062] The mass fraction of the carbon nanotube dispersion is 20-22%;

[0063] The concentration of sodium silicate solution is 2-2.5 mol / L;

[0064] Adding the sodium silicate solution dropwise into the carbon nanotube dispersion at a silicon dioxide / carbon nanotube mass ratio of 1-1.5%;

[0065] The amount of aluminum sulfate and sodium hydroxide added is such that the mass ratio of aluminum oxide to carbon nanotubes in the control system is 3-4%;

[0066] High-speed centrifugal speed is 8000r / min;

[0067] The high temperature calcination temperature is 550-600°C and the time is 40 minutes.

[0068] The preparation method of the modified polyurea binder is as follows:

[0069] First, the composite polyether polyol is added into a reaction kettle, and then isophorone diisocyanate is added into the reaction kettle, and stirred for reaction to obtain a prepolymer;

[0070] Add urea and bis(4-aminophenyl) disulfide to dimethylacetamide, stir and mix well to obtain an intermediate;

[0071] The intermediate was added to the prepolymer, the temperature was adjusted to 80° C., the mixture was stirred for 30 minutes and cooled to room temperature to obtain a modified polyurea binder.

[0072] The molar ratio of the composite polyether polyol to isophorone diisocyanate is 3:1;

[0073] The mixing ratio of urea, bis(4-aminophenyl) disulfide and dimethylacetamide is 10 g:4 g:100 mL;

[0074] The mixing mass ratio of the prepolymer to the intermediate is 1:5-6.

[0075] The preparation method of composite polyether polyol is as follows:

[0076] Add diethylene glycol to the reactor, and then add soybean oil, castor oil and water, adjust the temperature to 78°C, keep warm and stir for 30 minutes, then add sucrose, pass nitrogen into the reactor, exhaust the air in the reactor, evacuate to 0.5Pa, then pass dimethylamine, adjust the temperature to 98°C, and then add propylene oxide dropwise while stirring. After the addition is completed, heat to 120°C, continue stirring for 40 minutes, adjust the pressure to 0.3MPa, the temperature to 112°C, continue to keep warm and stir for 4 hours, and then dry for 1 hour to obtain a composite polyether polyol.

[0077] The weight parts of the raw materials of the composite polyether polyol are respectively:

[0078] 5 parts of diethylene glycol, 12 parts of soybean oil, 18 parts of castor oil, 4.5 parts of water, 25.5 parts of sucrose, 1.2 parts of dimethylamine, and 51.3 parts of propylene oxide.

[0079] The plasticizer is dioctyl terephthalate.

[0080] The production process of the silent LVT floor includes: hot pressing the PVC wear-resistant layer, the adhesive layer and the base material layer to obtain a slab;

[0081] The slab is then cured for 12 hours, then rolled with UV paint, tempered, cured for 24 hours, and then punched, trimmed, coated and packaged to complete.

[0082] The hot pressing temperature is 145-150°C and the pressure is 8-10MPa;

[0083] The health-preserving temperature is 25°C;

[0084] The lamination is carried out by using a self-adhesive EVA film for lamination packaging.

[0085] Wear-resistant layer thickness: 3.50±0.02mm;

[0086] The thickness of the bonding layer is 0.3±0.02mm;

[0087] The thickness of the base material layer is 6.00±0.05mm;

[0088] UV, tempering line

[0089] UV paint quantity 20±5g / ㎡;

[0090] Tempering: The floor outlet temperature is above 80℃, and the treatment time in hot water is more than 4 minutes;

[0091] Before punching and cutting: confirm that the curing time is sufficient, the physical properties meet the requirements, and the surface temperature of the material is around 25°C, otherwise punching and cutting is not allowed;

[0092] Straightness of right angle: measured with the right angle support of the assembly table, 1220 length ± 0.10mm, 1524 length ± 0.15mm;

[0093] Flatness: measured with a feeler gauge, required to be ≤0.50mm.

[0094] The following are specific embodiments

[0095] Example 1

[0096] The soundproof LVT floor includes: a PVC wear-resistant layer, an adhesive layer, and a base material layer which are laminated and compounded;

[0097] The PVC wear-resistant layer is made of the following ingredients by weight: 50 parts of PVC powder, 10 parts of plasticizer, and 8 parts of nanocomposite material;

[0098] The PVC wear-resistant layer is prepared by putting the above materials into an internal mixer, mixing at 185°C, and then calendering through a five-roll calender;

[0099] The bonding layer adopts: modified polyurea adhesive;

[0100] The base material layer is made of the following ingredients by weight: 30 parts of stone powder, 30 parts of PVC powder, and 10 parts of plasticizer.

[0101] The preparation method of nanocomposite material is as follows:

[0102] First, carbon nanotubes are uniformly dispersed in deionized water to obtain a carbon nanotube dispersion, the pH of the carbon nanotube dispersion is adjusted to 9.8, the temperature is adjusted to 80° C., and the dispersion is kept warm for later use;

[0103] Adding sodium silicate to deionized water, stirring and mixing evenly to obtain a sodium silicate solution;

[0104] The sodium silicate solution is added dropwise to the carbon nanotube dispersion while stirring. After the addition is completed, stirring is continued for 1 hour, and the mixture is allowed to stand for 2 hours. Then, aluminum sulfate and sodium hydroxide are added and stirring is continued for 1 hour. Then, the pH value of the system is adjusted to neutral, and the mixture is allowed to stand for 4 hours. The mixture is subjected to high-speed centrifugation for 30 minutes, filtered, washed with water, dried, calcined at high temperature, and cooled to obtain a nanocomposite material.

[0105] The mass fraction of carbon nanotube dispersion is 20%;

[0106] The concentration of sodium silicate solution is 2 mol / L;

[0107] Adding the sodium silicate solution dropwise into the carbon nanotube dispersion at a silicon dioxide / carbon nanotube mass ratio of 1%;

[0108] The amount of aluminum sulfate and sodium hydroxide added is such that the mass ratio of aluminum oxide to carbon nanotubes in the control system is 3%;

[0109] High-speed centrifugal speed is 8000r / min;

[0110] The high temperature calcination temperature is 550°C and the time is 40 minutes.

[0111] The preparation method of the modified polyurea binder is as follows:

[0112] First, the composite polyether polyol is added into a reaction kettle, and then isophorone diisocyanate is added into the reaction kettle, and stirred for reaction to obtain a prepolymer;

[0113] Add urea and bis(4-aminophenyl) disulfide to dimethylacetamide, stir and mix well to obtain an intermediate;

[0114] The intermediate was added to the prepolymer, the temperature was adjusted to 80° C., the mixture was stirred for 30 minutes and cooled to room temperature to obtain a modified polyurea binder.

[0115] The molar ratio of the composite polyether polyol to isophorone diisocyanate is 3:1;

[0116] The mixing ratio of urea, bis(4-aminophenyl) disulfide and dimethylacetamide is 10 g:4 g:100 mL;

[0117] The mixing mass ratio of the prepolymer to the intermediate is 1:5.

[0118] The preparation method of composite polyether polyol is as follows:

[0119] Add diethylene glycol to the reactor, and then add soybean oil, castor oil and water, adjust the temperature to 78°C, keep warm and stir for 30 minutes, then add sucrose, pass nitrogen into the reactor, exhaust the air in the reactor, evacuate to 0.5Pa, then pass dimethylamine, adjust the temperature to 98°C, and then add propylene oxide dropwise while stirring. After the addition is completed, heat to 120°C, continue stirring for 40 minutes, adjust the pressure to 0.3MPa, the temperature to 112°C, continue to keep warm and stir for 4 hours, and then dry for 1 hour to obtain a composite polyether polyol.

[0120] The weight parts of the raw materials of the composite polyether polyol are respectively:

[0121] 5 parts of diethylene glycol, 12 parts of soybean oil, 18 parts of castor oil, 4.5 parts of water, 25.5 parts of sucrose, 1.2 parts of dimethylamine, and 51.3 parts of propylene oxide.

[0122] The plasticizer is dioctyl terephthalate.

[0123] The production process of the silent LVT floor includes: hot pressing the PVC wear-resistant layer, the adhesive layer and the base material layer to obtain a slab;

[0124] The slab is then cured for 12 hours, then rolled with UV paint, tempered, cured for 24 hours, and then punched, trimmed, coated and packaged to complete.

[0125] The hot pressing temperature is 145°C and the pressure is 8MPa;

[0126] The health-preserving temperature is 25°C;

[0127] The lamination is carried out by using a self-adhesive EVA film for lamination packaging.

[0128] Example 2

[0129] On the basis of Example 1, the difference from Example 1 is that the PVC wear-resistant layer is made of the following components by weight: 52 parts of PVC powder, 13 parts of plasticizer, and 10 parts of nano-composite material;

[0130] The base material layer is made of the following ingredients by weight: 32 parts of stone powder, 32 parts of PVC powder, and 11 parts of plasticizer.

[0131] Example 3

[0132] On the basis of Example 1, the difference from Example 1 is that the PVC wear-resistant layer is made of the following components by weight: 58 parts of PVC powder, 14 parts of plasticizer, and 10 parts of nano-composite material;

[0133] The base material layer is made of the following ingredients by weight: 31 parts of stone powder, 33 parts of PVC powder, and 11 parts of plasticizer.

[0134] Example 4

[0135] On the basis of Example 1, the difference from Example 1 is that the PVC wear-resistant layer is made of the following components by weight: 60 parts of PVC powder, 15 parts of plasticizer, and 12 parts of nano-composite material;

[0136] The base material layer is made of the following ingredients by weight: 35 parts of stone powder, 35 parts of PVC powder, and 12 parts of plasticizer.

[0137] Comparative Example 1:

[0138] On the basis of the technical solution of Example 1, the nanocomposite material is replaced by carbon nanotubes in equal amounts, and the rest of the technical solutions remain unchanged.

[0139] Comparative Example 2:

[0140] Based on the technical solution of Example 1, no composite polyether polyol is added, and the rest of the technical solutions remain unchanged.

[0141] Comparative Example 3:

[0142] On the basis of the technical solution of Example 1, the composite polyether polyol is replaced by a conventional commercially available polyether polyol (molecular weight of 4800, model number 104G), and the rest of the technical solutions remain unchanged.

[0143] test:

[0144] Mechanical properties test

[0145] According to the national standard GB / T15104-2006 "Decorative veneer veneer artificial board", the immersion peeling test and surface bonding strength test were carried out using a mechanical testing machine. The test results are shown in Table 1:

[0146] Table 1

[0147] Bonding strength MPa Example 1 2.54 Example 2 2.50 Example 3 2.52 Example 4 2.49 Comparative Example 1 2.36 Comparative Example 2 1.89 Comparative Example 3 2.23

[0148] It can be seen from Table 1 that the floor prepared by the present invention has excellent gluing performance.

[0149] Sound absorption performance test

[0150] According to GB / T18696.1-2004 "Measurement of sound absorption coefficient and acoustic impedance in acoustic impedance tubes Part 1: Standing wave ratio method", the sound absorption coefficient of wood-plastic materials at various frequencies was tested. The test environment was a semi-anechoic room, with a temperature of 15°C, a humidity of 20%, an atmospheric pressure of 100.76kPa, and a measurement range of 100-2000Hz. The frequency of the highest sound absorption coefficient was compared:

[0151] Table 2

[0152] Highest sound absorption coefficient Example 1 0.43 Example 2 0.41 Example 3 0.45 Example 4 0.42 Comparative Example 1 0.26 Comparative Example 2 0.31 Comparative Example 3 0.40

[0153] It can be seen from Table 2 that the floor prepared by the present invention has a maximum sound absorption coefficient of more than 0.41 after being measured at different frequencies, and has a good sound absorption effect.

[0154] Taking Example 1 as the basic sample, the effects of different nanocomposite addition amounts on the maximum sound absorption coefficient were compared;

[0155] Table 3

[0156] Weight Highest sound absorption coefficient 0 0.24 4 0.35 8 0.43 12 0.42 16 0.38 20 0.31

[0157] It can be seen from Table 3 that with the increase of the content of nanocomposite materials, the sound absorption performance of the floor first increases and then gradually decreases.

[0158] The above description is only a preferred embodiment of the present invention, but the present invention is not limited to the scope of implementation shown. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which still do not exceed the spirit covered by the specification, should be within the protection scope of the present invention.

Claims

1. Silent LVT floor, characterized by: include: The PVC wear-resistant layer, adhesive layer and base material layer are laminated and compounded; The PVC wear-resistant layer is made of the following ingredients by weight: 50-60 parts of PVC powder, 10-15 parts of plasticizer, and 8-12 parts of nanocomposite material; The bonding layer adopts: modified polyurea adhesive; The base material layer is made of the following ingredients by weight: 30-35 parts of stone powder, 30-35 parts of PVC powder, and 10-12 parts of plasticizer.

2. The sound-proof LVT floor according to claim 1, characterized in that: The nanocomposite material preparation method is: First, carbon nanotubes are uniformly dispersed in deionized water to obtain a carbon nanotube dispersion, the pH of the carbon nanotube dispersion is adjusted to 9.8, the temperature is adjusted to 80° C., and the dispersion is kept warm for later use; Adding sodium silicate to deionized water, stirring and mixing evenly to obtain a sodium silicate solution; The sodium silicate solution is added dropwise to the carbon nanotube dispersion while stirring. After the addition is completed, stirring is continued for 1 hour, and the mixture is allowed to stand for 2 hours. Then, aluminum sulfate and sodium hydroxide are added and stirring is continued for 1 hour. Then, the pH value of the system is adjusted to neutral, and the mixture is allowed to stand for 4 hours. The mixture is subjected to high-speed centrifugation for 30 minutes, filtered, washed with water, dried, calcined at high temperature, and cooled to obtain a nanocomposite material.

3. The sound-proof LVT floor according to claim 2, characterized in that: The mass fraction of the carbon nanotube dispersion is 20-22%; The concentration of sodium silicate solution is 2-2.5 mol / L; Adding the sodium silicate solution dropwise into the carbon nanotube dispersion at a silicon dioxide / carbon nanotube mass ratio of 1-1.5%; The amount of aluminum sulfate and sodium hydroxide added is such that the mass ratio of aluminum oxide to carbon nanotubes in the control system is 3-4%; High-speed centrifugal speed is 8000r / min; The high temperature calcination temperature is 550-600°C and the time is 40 minutes.

4. The sound-proof LVT floor according to claim 1, characterized in that: The modified polyurea binder preparation method is: First, the composite polyether polyol is added into a reaction kettle, and then isophorone diisocyanate is added into the reaction kettle, and stirred for reaction to obtain a prepolymer; Add urea and bis(4-aminophenyl) disulfide to dimethylacetamide, stir and mix well to obtain an intermediate; The intermediate was added to the prepolymer, the temperature was adjusted to 80° C., the mixture was stirred for 30 minutes and cooled to room temperature to obtain a modified polyurea binder.

5. The sound-proof LVT floor according to claim 4, characterized in that: The molar ratio of the composite polyether polyol to isophorone diisocyanate is 3:1; The mixing ratio of urea, bis(4-aminophenyl) disulfide and dimethylacetamide is 10 g:4 g:100 mL; The mixing mass ratio of the prepolymer to the intermediate is 1:5-6.

6. The sound-proof LVT floor according to claim 5, characterized in that: The preparation method of the composite polyether polyol is as follows: Add diethylene glycol to the reactor, and then add soybean oil, castor oil and water, adjust the temperature to 78°C, keep warm and stir for 30 minutes, then add sucrose, pass nitrogen into the reactor, exhaust the air in the reactor, evacuate to 0.5Pa, then pass dimethylamine, adjust the temperature to 98°C, and then add propylene oxide dropwise while stirring. After the addition is completed, heat to 120°C, continue stirring for 40 minutes, adjust the pressure to 0.3MPa, the temperature to 112°C, continue to keep warm and stir for 4 hours, and then dry for 1 hour to obtain a composite polyether polyol.

7. The sound-proof LVT floor according to claim 6, characterized in that: The weight parts of the raw materials of the composite polyether polyol are respectively: 5 parts of diethylene glycol, 12 parts of soybean oil, 18 parts of castor oil, 4.5 parts of water, 25.5 parts of sucrose, 1.2 parts of dimethylamine, and 51.3 parts of propylene oxide.

8. The sound-proof LVT floor according to claim 1, characterized in that: The plasticizer is dioctyl terephthalate.

9. The production process of the silent LVT floor according to claim 1, characterized in that: include: The PVC wear-resistant layer, the adhesive layer and the base material layer are hot-pressed to obtain a slab; The slab is then cured for 12 hours, then rolled with UV paint, tempered, cured for 24 hours, and then punched, trimmed, coated and packaged to complete.

10. The production process of the silent LVT floor according to claim 9, characterized in that: The hot pressing temperature is 145-150°C and the pressure is 8-10MPa; The health-preserving temperature is 25°C; The lamination is carried out by using a self-adhesive EVA film for lamination packaging.

Citation Information

Patent Citations

  • Manufacturing method of hard PVC floor

    CN108177289A

  • Preparation method of high-flame-retardant smoke-suppression LVT floor wear-resistant layer

    CN111761772A

  • Insulated wire material resistant to high-temperature aging and cracking

    CN118994812A

  • Thermal insulation floor for building and preparation method of thermal insulation floor

    CN119081488A

  • Degradable automobile floor mat material and preparation method therefor

    WO2023240669A1